Study of Different Parametric Variations of MOSFET Pressure Sensor - Shruti Bhargava; Spv Subbarao (Institute of Advanced Engineering and Science, 2018)
There is a growing demand of miniaturization of the electronics world. A brief discussion for simulating and fabrication of the MOSFET based pressure sensor in nanoscale is being reviewed in this paper. Aim of this paper is to collect all the scaling challenges and their solutions together to make understanding the facts of the MOSFET based sensor. As the MOSFET move from micro scale to nanoscale the functioning changes dramatically. The Silicon oxide material fails when scale down to nano region. However, many issues such as electrical quality , thermodynamic stability, Kinetic stability, gate compatibility and process compatibility were being solved in the process of integration and implementation.